Analisis Kesalahan Berbahasa Tataran Fonologi Pidato Prabowo Subianto Di Kanal YouTube Kompas TV - Rahayu, Indah Eka; Hermaliza, Hermaliza (UIR Press, 2024)
The analysis of language errors at the level of phonology is to identify and understand errors that occur in the production or recognition of language sounds. Through phonological analysis, these errors can be analyzed systematically to identify the underlying patterns and rules. The problem in this study is how are the language errors of phoneme change at the phonological level in Prabowo Subianto's speech on the Kompas TV YouTube channel? The approach in this research is a qualitative approach with the method used in this research is descriptive qualitative method. The data taken in this study are words that are pronounced or spoken that are not in accordance with the rules of language, especially at the level of phonology. The data collection techniques used in this research are: documentation techniques, listening techniques and note-taking techniques. The data analysis technique used is qualitative descriptive technique using the theory of Miles and Hubermen (1984). Based on the results of the study, it can be concluded that there are 68 language error data. 1) There are 27 phoneme changes error data, 2) There are 29 phoneme omission errors, 3) There are 12 phoneme addition errors. Of the 12 error data, the writer only found consonant phoneme addition errors. Besides, the writer did not find any error data of vowel phoneme addition, vowel series formation and consonant cluster formation from single consonant phoneme.